Olive oil: a review on the identity and quality of olive oils produced in Brazil - Paula Freitas Filoda; Fabio Clasen Chaves; Jessica Fernanda Hoffmann; Cesar Valmor Rombaldi (Revista Brasileira de Fruticultura, 2021)
Abstract The sensory quality of olive oils is influenced by the diversity and concentration of volatile and non-volatile compounds that vary according to cultivar, and edaphic, climatic, and cultivation conditions, which allows for establishing the origin of the product. In addition, since this crop has been recently introduced in Brazil, little is known about the performance of cultivars in this region, where investments in this activity have been made. Thus, relevant aspects about the chemical and sensory quality of olive oils are presented and discussed, as well as how these aspects influence the identity of the product.